STRENGTH COMPARISONS BETWEEN ROLLED SAND CONCRETE AND DUNE SAND CONCRETE - GUETTALA, A.; MEZGHICHE, B.; CHEBILI, R. (Courrier du Savoir; Vol. 2 (2002): Courrier du Savoir)
The objective of using sand concrete is to reduce costs especially in sand rich regions where transportation costs of aggregates over long distances makes any construction too expensive. This paper presents the mechanical characteristics of two types of sand concrete, a sand concrete based on rolled sand and dune sand concrete, and compares these two types of sand concretes. It is also intended to determine the influence of the water/cement (0.4, 0.45, 0.5), cement/ sand (1/3, 1/4) and additives (plasticizers and thinners) on the mechanical characteristics: Compression and tension. It is observed that the cube strength rises with respect to time for the two types of sand concrete. The cube strength diminishes when increasing the water/ cement for rolled sand concrete and increases for the dune sand concrete. The influence of additives is quite noticeable; the rise in the cube strength is about 40 %. Taking into consideration these results, it is then recommended for the users the exploitation of rolled sand concrete with or without additives, however for the dune sand concrete, the use of additives is most important.